PENINGKATAN KEMAMPUAN GURU SDN 006 SENCANO JAYA DALAM MEMBUAT RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERBASIS INKUIRI - Yusrizal Yusrizal (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
This research was carried out with the aim of increasing the ability of teachers to make lesson plans (RPP) using inquiry-based learning models, this inquiry-based learning model will have a learning impact on students' positive mental development, because through this learning, students have wide opportunities. to find and find for themselves what he needs, especially in abstract learning. The form of research undertaken was School Action Research (PTS) with 2 cycles. This research was conducted at SDN 006 Sencano Jaya, Batang Peranap District, Indragiri Hulu Regency with a sample size of 9 teachers. Based on the analysis of research data after applying the inquiry learning model, the ability of teachers to make lesson plans, that refer to Permendikbud Number 22 of 2016, has shown an increase, from cycle I to Cycle II. Cycle I to cycle II has increased. In the first cycle the teacher's average score was 71.66, and in the second cycle it increased to 85.00. Likewise, Classical Absorption (DSK) has increased. In the first cycle, the DSK was 35.00%, and in the second cycle it increased to 59.44%. So it can be concluded that this inquiry-based learning model by providing guidance and direction to teachers at SDN 006 Sencano Jaya can be said to be successful because it has increased from cycle I to cycle II.